Bølgende moderskab: Moderskabslitteratur i 1970’erne og kanoniseringens tidsligheder - Dolmer, Ida Aaskov (Passage - Tidsskrift for litteratur og kritik, 2025)
“Motherhood in Waves: Recontextualization of Women’s Literature in the 1970s” This article examines what has been framed as Danish ‘motherhood literature’ from the 1970s. The article argues that this frame is a product of the literary works’ cri- tical reception of the last decade, and not a frame originating in the 1970s. A fra- mework is thus formed for a current wave of motherhood literature, mimicking the wave metaphor in feminism. From this follows a discussion of the temporality and historicity of texts, in which it is proposed that the wave metaphor cannot fully ac- count for the ways in which texts are formed by and connected to many different understandings of time.